Hyperexcitability of Sensory Neurons in Fragile X Mouse Model - Deng, Pan-Yue; Avraham, Oshri; Cavalli, Valeria; Klyachko, Vitaly A. (Frontiers in Molecular Neuroscience, 2021)
Sensory hypersensitivity and somatosensory deficits represent the core symptoms of Fragile X syndrome (FXS). These alterations are believed to arise from changes in cortical sensory processing, while potential deficits in the function of peripheral sensory neurons residing in dorsal root ganglia remain unexplored. We found that peripheral sensory neurons exhibit pronounced hyperexcitability in Fmr1 KO mice, manifested by markedly increased action potential (AP) firing rate and decreased threshold. Unlike excitability changes found in many central neurons, no significant changes were observed in AP rising and falling time, peak potential, amplitude, or duration. Sensory neuron hyperexcitability was caused primarily by increased input resistance, without changes in cell capacitance or resting membrane potential. Analyses of the underlying mechanisms revealed reduced current mediated by HCN channels and reduced expression of HCN1 and HCN4 in Fmr1 KO compared to WT. A selective HCN channel blocker abolished differences in all measures of sensory neuron excitability between WT and Fmr1 KO neurons. These results reveal a hyperexcitable state of peripheral sensory neurons in Fmr1 KO mice caused by dysfunction of HCN channels. In addition to the intrinsic neuronal dysfunction, the accompanying paper examines deficits in sensory neuron association/communication with their enveloping satellite glial cells, suggesting contributions from both neuronal intrinsic and extrinsic mechanisms to sensory dysfunction in the FXS mouse model.